Role and efficacy of vaginal dinoprostone gel (PGE2) plus vaginal misoprostol (PGE1) in second trimester termination of pregnancy - Kumar, Abhijeet; Agarwal, Raju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The addition of dinoprostone gel (PGE2) to standard regimen of second trimester abortion using vaginal misoprostol (PGE1) reduces failure rate and decrease induction abortion time interval. We evaluated the role and efficacy of vaginal dinoprostone gel with vaginal misoprostol in women undergoing second trimester abortion. Objective of present study was to assess the safety and effectiveness of vaginal dinoprostone gel plus vaginal misoprostol for second trimester termination of pregnancy. Methods: This study was a prospective cohort involving 100 women with 12-20 weeks gestation requesting termination of pregnancy. In study group 0.5mg dinoprostone gel applied vaginally followed by 400µg misoprostol every four hourly (max 3 doses) after six hours of dinoprostone gel application. The mean age of the women study was 27.2 years and mean gestational age was 18.9 weeks. The primary effectiveness of the study was the efficacy of the treatment to terminate pregnancy at 20 hrs. Secondary outcomes were induction abortion interval, failure rate, side effects. statistical analysis of study was carried out using chi square test. Results: At 20 hours, the complete abortion rate was 100%. Within 16 hours 98% women aborted without any significant side effects. Mean induction abortion interval was 14.56 hours. Conclusions: Combination of vaginal dinoprostone gel (PGE2) plus misoprostol (PGE1) is effective, safe and alternate method for second trimester pregnancy termination with. In this protocol induction to abortion interval time is less as compared to other methods of second trimester pregnancy termination.